Tolerance Villages in Bandung: Fostering Interfaith Harmony and Multicultural Awareness - Feraswari, Ariessa Rantau; Kustana, Kustana (Prodi Magister Sosiologi UIN Sunan Gunung Djati Bandung, 2026)
Bandung is a multicultural city with high religious, ethnic, and cultural diversity. However, this condition also gives rise to the potential for intolerance, which has received serious attention in recent years. In response, the Bandung City Government initiated the Tolerance Village to strengthen interfaith harmony and increase community multicultural awareness. By 2025, six villages had been inaugurated. This study aims to examine the role of the Tolerance Village in maintaining harmony, increasing multicultural awareness, and comparing similarities and differences between the six locations. The research method used was a qualitative descriptive, comparative case study. Data were collected through interviews, field observations, and document analysis. The results show that the Tolerance Village contributes positively to the creation of interfaith dialogue spaces, strengthening diversity-based social interactions, and multicultural education at the community level. However, budget limitations, resistance from some groups, and lack of program sustainability are obstacles that need to be overcome. This study concludes that Tolerance Village can serve as an innovative social model for building urban harmony. This program needs to be expanded to other areas by strengthening stakeholder collaboration to make Bandung more inclusive, tolerant, and sustainable.